Performance Evaluation of AODV Routing Protocol for Mobile Wireless Sensor Network - Mohamad Nazim, Jambli; Kartinah, Zen; Halikul, Lenando; Tully, Alan (IEEE, 2011)
Topology change is the main factor that affects the network life time of Wireless Sensor Network (WSN) applications. In static WSN, the topology change is often caused by node failure which is due to energy depletion. However, in the Mobile WSN (MWSN), the main reason of the topology change is caused by the node movement. Since the mobile sensor nodes are limited in power supply and have a low radio frequency coverage, they are easily losing their connection with neighbours, and have difficulties updating their routing tables. The switching process from one coverage area to another consumes more energy that related to transmitting and receiving association packets. Using Ad hoc On-Demand Distance Vector (AODV) routing protocol in MWSN application shows degradation in network performance due to high density and speed of mobile nodes. In this paper, through extensive simulation we evaluated the capability of AODV on how far it can react to network topology change in MWSN. We investigated the performance metrics namely packet loss and energy consumption of mobile nodes with various speed, density and route update interval (RUI). Our performance study demonstrates that by applying the existing AODV in MWSN, the results show a high percentage of packet loss and the reduction in total network energy consumption of mobile nodes if RUI is getting longer due to serious broken link caused by nodes movement. We also identify some key research problems that need to be addressed for successful implementation of AODV in MWSN.